The problem of the acceptance of the non-punitive victim in the criminal justice system - Xavier, José Roberto (Revista da Faculdade de Direito do Sul de Minas, 2018)
The social category victims of criminal actions has gained a lot of visibility in the last two decades. The emergence of victims movements, the exploitation of victims dramas in the media, the quests for legal changes to protect or in consideration of the victims, these are all scenarios that have become more frequent in many different countries from different legal traditions. But this visibility brings some challenges and inconveniences for the traditional actors of the criminal justice system. For judges and prosecutors, it seems that more often than not the victims are perceived as a problematic new actor that should remain estranged from the process of imposing a criminal punishment. It is a new actor in the scene, and an actor who does not have an established legitimacy when it comes to determining a criminal punishment. The process of sentencing is not theoretically speaking concerned with the desire of the victim to make the criminal suffer. In short, the inconvenience that the victim poses to the criminal justice system would come from its novelty and also from its (perceived) strong punitive feelings. But, and here is the theme of this article, what happens with the criminal justice system when it faces a victim that does not want punishment, a victim that demands a different solution? How do judges react to a victim that is ready to compose, to forgive or to do not seek a punishment in any sense? To answer or, more accurately speaking, to develop these questions, we use the data from some qualitative interviews with judges and prosecutors in a Civil Law tradition country (Brazil) that were collected in the context of our doctoral research. We intend to raise questions about how the criminal justice system, specifically in matters of sentencing, deals with non-punitive victims and, more importantly, how it perceives solutions that depart from the frame of the modern theories of punishment and its traditional punishments. Can the criminal justice system accept a victims pardon, composition or lack of interest in pursuing a criminal punishment as a solution to the conflict? Can it conceive that the interest of society sometimes may worsen a conflict more than bring any form of solution? And can we conceive that, despite all the mediatized punitive portray of the victims, some of them are looking for a solution of a conflict that differs from the traditional infliction of punishment, the only option that criminal justice system seems to offer?